(untitled) (Ustozlar uchun, 2025)
This study explores the profound influence of World War II on English literature, emphasizing thematic, stylistic, and psychological transformations that emerged during and after the war. The conflict reshaped literary perspectives by confronting writers with violence, trauma, loss, and moral ambiguity. Postwar literature reflects a deep concern with human suffering, existential anxiety, identity crisis, and the collapse of traditional values. The study highlights how both soldier-writers and civilian authors contributed to a new literary voice that questioned authority, celebrated resilience, and examined the complexities of modern human experience